Docking to an underwater suspended charging station: Systematic design and experimental tests. (1st April 2022) - Lin, Mingwei; Lin, Ri; Yang, Canjun; Li, Dejun; Zhang, Zhuoyu; Zhao, Yucheng; Ding, Wangjie
Abstract: Using seafloor docking stations to automatedly recover and recharge autonomous underwater vehicles (AUV) is an emerging technology to solve the problem of energy limitation for persistent observation. However, this operational modality would constrain the range of AUV activity within a certain radius centered of the seafloor docking station. To increase the recovery flexibility of AUV, this paper demonstrates a concept of docking to a suspended underwater charging station, which is fixed on a taut rope from a surface vessel. This study provides some critical design steps of the AUV docking system, including the construction of the platforms, the guidance method, the collision analysis of docking operation, as well as the rotation-adaptive contactless power/data transfer method. The feasibility of the system was verified in Qingjiang River. Aided by a re-attempt mechanism, the success rate of docking to the cone-type entrance of the suspended station is 100% (39 of 39 tests) after the surface vessel was anchored and the operating depth was over 30-m. The maximum contactless charging power is 882 W with an efficiency of 81.3%, and the maximum data transmission rate is of approximately 41.1 Mbps at different roll angle of AUV. Highlights: The effects of cable length, mass ratio of AUV to DS, and the lateral deviation on the docking operations are analyzed to guide the design of the suspended AUV docking system. We propose the optimization design for the transition phase and docking phase to improve the success rate of docking operations. In addition, three path planning strategies for the home phase are compared to figure out their suitable application scenarios. A rotation adaptive idea is included in the design of the contactless power/data transfer devices to lower the pose alignment requirement when AUV docks to the station.